Soil organic carbon changes following degradation and conversion to cypress and tea plantations in a tropical mountain forest in Kenya - Chiti, T.; Díaz Pinés, Eugenio; Butterbach-Bahl, Klaus; Marzaioli, F.; Valentini, R. (Springer, 2018)
Aims This study investigates, in a montane forest in Kenya, the changes in amount and stability of soil organic carbon (SOC) as a consequence of: a) forest degradation, by comparing primary and degraded forests; b) the replacement of degraded forests with cypress and tea plantations, by considering sites installed at different time in the past. Methods The SOC concentrations and stocks were determined in different layers to 1 m depth, and the SOC turnover time (TT) derived by measuring the 14C concentration in the layers within the 0–30 cm depth. Results A significant SOC decline was evident in the 0–5 and 5–15 cm layers of degraded forest while, on the long term, both plantations induced a significant SOC increase in the 0–30 cm depth. The longer TT’s and lower SOC concentrations in the upper layers of degraded rather than primary forests imply an impact of forest degradation on the decomposition of the fast cycling SOC. Similarly, the shorter TT with increasing plantations age implies differences in SOC stabilization mechanisms between plantations and forests. Conclusions Cypress and tea plantations established on degraded forests stimulate a long term SOC accrual but at the same time decrease the stability of the SOC pool.